Prevalence of diabetes and pre-diabetes in Greece. Results of the First National Survey of Morbidity and Risk Factors (EMENO) study. (February 2021) - Makrilakis, Konstantinos; Kalpourtzi, Natasa; Ioannidis, Ioannis; Iraklianou, Stella; Raptis, Athanasios; Sotiropoulos, Alexis; Gavana, Magda; Vantarakis, Apostolos; Kantzanou, Maria; Hadjichristodoulou, Christos; Chlouverakis, Grigoris; Trypsianis, Grigoris; et al.
Highlights: Nation-wide representative data are needed to capture prevalence of diabetes and pre-diabetes correctly. Total diabetes prevalence in Greece was found at 11.9%. Pre-diabetes prevalence was found at 12.4%. Unknown diabetes prevalence was low (1.5%). Abstract: Aims: To report the results of the first national Health Examination Survey (HES) on the prevalence of diabetes, its pharmacologic treatment and level of control, as well as pre-diabetes in Greece. Methods: Data were derived from the National Survey of Morbidity and Risk Factors (EMENO), in a randomly selected, representative sample of the adult Greek population. Sampling weights were applied to adjust for study design and post-stratification weights to match sample age/sex distribution to the population. Non-response was adjusted by inverse probability weighting. Weighted prevalence estimates are provided. Results: A total of 4393 persons with HbA1c and/or fasting plasma glucose measurements were included. Total diabetes prevalence was 11.9% (95% CI: 10.9–12.9), known diabetes 10.4% (9.5–11.4), and unknown 1.5% (1.1–1.9), with considerable increase in older age groups and no difference between genders. Pre-diabetes prevalence was 12.4% (11.4–13.6). The majority of persons with known diabetes were receiving metformin. Of those with known diabetes (and measured HbA1c), 70.9% were well controlled (HbA1c <7.0%). Conclusions: This first representative national HES showed high prevalence of diabetes in Greece, with low prevalence of unknown diabetes. Pre-diabetes prevalence is also substantial. These results will hopefully enable national authorities develop tailored and efficient strategies for disease prevention and management.